Sedimentary vanadium depletion under sulfidic conditions : Implications for (paleo)redox proxy applications - van Helmond, Niels A.G.M.; Żygadłowska, Olga M.; Lenstra, Wytze K.; Klomp, Robin; Humborg, Christoph; Conley, Daniel J. ; 0000-0001-9668-9284; Jetten, Mike S.M.; Slomp, Caroline P. (Geochimica et Cosmochimica Acta, 2025)
Sedimentary concentrations of redox-sensitive trace metals are widely used to reconstruct past ocean redox conditions. Vanadium (V) has great potential as a (paleo)redox proxy, due to its strong redox-dependent speciation (+III, +IV, +V) and the increased sedimentary sequestration of its more reduced species. The geochemistry of V in sulfide-rich marine environments is not yet well understood, however, hampering the use of V as a (paleo)redox proxy. Here, we present V data for two coastal systems, with bottom water redox conditions ranging from oxic to euxinic, to further constrain V geochemistry. Our sedimentary record from a eutrophic coastal marine basin (Scharendijke basin, Lake Grevelingen, the Netherlands), covering the last decade, shows distinct enrichments in molybdenum (Mo) and organic carbon (Corg) but depletions in V during seasonal bottom water euxinia, which can be discerned due to the exceptionally high sedimentation rate at our study site (up to 20 cm yr−1). A seasonal study for the same coastal basin confirms this trend and reveals the accumulation of V, iron (Fe) and manganese (Mn) in the water column during summer euxinia. We conclude that the slow kinetics of V reduction to V(III) and subsequent precipitation as (oxy)hydroxide V(OH)3(s) likely provide the opportunity for V to escape sedimentary sequestration during summer euxinia, resulting in the observed sedimentary V depletion. Sediments from three sites with contrasting bottom water redox conditions (oxic, seasonally hypoxic, euxinic) in the eutrophic Stockholm Archipelago, show a similar trend as that of Lake Grevelingen, with decreasing V concentrations and increasing Mo and Corg concentrations as bottom water conditions become more reducing. This confirms that our findings for Lake Grevelingen are not site-specific and are likely a generic feature of euxinic coastal systems with high sulfide concentrations (> 0.5 mmol L−1) near the sediment surface and high rates of anaerobic degradation of organic matter. Our results show that co-occurring sedimentary Mo and Corg enrichments and V depletion (or absence or suppression of an enrichment) are indicators of strongly sulfidic conditions in such settings. Finally, we show that maxima in sedimentary molar V/Mn ratios correlate with strongly reducing conditions. This finding contrasts with prior work on V/Mn ratios as a (paleo)redox proxy, implying that further research is necessary.
Keywords: (paleo)redox proxy; Deoxygenation; Molar V/Mn ratio; Sediments; Sulfide; Trace metals; Vanadium